From Dusty Shelves to Dynamic Spaces: The Innovative Journey of the Project Re:Booking to Revitalise the Book Collection of the VU University Library - Oldenhof, David (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
Many libraries face the challenge to deal with the often massive but very little used print collection. At the Vrije Universiteit Amsterdam (VU), the library started the three-year project Re:Booking to repurpose the print collection in new and innovative ways in close collaboration with communities throughout the university. In this practice paper, we outline our unusual approaches and present the results from the first two years of the project. With our paper, we hope to inspire other libraries to take a fresh look at the value of their print collections.